CRISPR/Cas9 gene editing therapies for cystic fibrosis. (3rd June 2021) - Graham, Carina; Hart, Stephen
Abstract: Introduction: Cystic fibrosis (CF) is a life-limiting genetic disorder affecting approximately 70, 000 people worldwide. Current burden of treatment is high. While the latest pharmaceutical innovation has benefitted many, patients with certain genotypes remain excluded. Gene editing has the potential to correct the underlying cause of disease for all patients, representing a permanent cure. Areas covered: Various DNA editing-based strategies for treatment are currently being developed. Different strategies are called for based upon location of mutations (intronic vs. exonic), delivery mechanism of editing machinery, and cell type being targeted. Furthermore, the unique physiology of the CF lung presents a variety of barriers to delivery of CRISPR-Cas9 machinery. Expert opinion: The most significant obstacle to the use of CRISPR-Cas9 in vivo is the fact that the most clinically relevant and accessible CF tissue, the airway epithelium, is made up of non-dividing cells where precise editing via homology-directed repair (HDR) does not occur; rather, potentially deleterious imprecise editing via non-homologous end joining (NHEJ) dominates. Future research should focus on the development of either more precise NHEJ-based approaches, access to airway basal cells, editing approaches that do not involve introducing genomic double-strand breaks, and strategies with ex vivo edited cells.